The role of the land layout parameters and production efficiency in the evaluation and shaping of the spatial structure of land - Gniadek, Jacek; Szewcz, Robert; Piech, Izabela (International Conference “Environmental Engineering”, 2017)
The article contains the results of the plots layout research in the farms of the selected object in the southern Poland. The basic surface element adopted for the research, were continuous parts of the registry plots covered by one form of use. To carry out tests on such a large number of plots specialized computer programs used, which use data from the digital cadastral map and the descriptive part of the land and buildings registry documentation kept in digital system. The applied technology allowed obtaining more than 70 features, characterizing each analyzed plot. Detailed studies included the 15 basic features of plots layout, first four of which determine the spatial parameters of the plot, three features relate to the estimated costs of cultivation dependent on its layout, the next two describe the location of the plot in the village and in the farm, and the last five characterize the farm, that owns the plot. The obtained result allowed the identification of positive and negative aspects of the tested ground system indicating the necessary changes in terms of its improvement.